Representasi Kekuasaan dalam Pidato Menteri Pendidikan Kebudayaan Riset dan Teknologi - Ilham Ilham; Anshari Anshari; Johar Amir (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study aims to describe the shape and form of representation of power in the speech of the Minister of Education, Culture, Research and Technology by using social change analysis from Norman Fairclough. The focus of this research is text analysis, text production, and sociocultural analysis with data in the form of power vocabulary. This research is a discourse analysis study in the form of critical discourse analysis (AWK). The source of the data for this study is the online media site Kemdikbud.go.id which contains the text of the speech including words, clauses and sentences. The research data were obtained by documentation, reading, and note-taking techniques. The results of the study show that there are features in the vocabulary of power that have experiential value in that they contain ideological words that are fought for, lexical processes, and the use of metaphors as a form of representation of power through language in the Minister of Education and Culture's speech. From a review of text production and socio-culture, it also shows that the production of discourse in speech is inseparable from aspects of power and domination. Both domination and power in groups or individuals.